(untitled) (Eduscotech, 2024)
This study examines the implementation of Islamic financial literacy based on financial socialization at SMK Maospati Magetan and analyzes its contribution to supporting the Sharia financial industry. Grounded in financial socialization theory, which identifies family, school, peers, and digital media as key socialization agents, the research employs a quantitative explanatory design to evaluate the influence of financial socialization on students’ Islamic financial literacy. Data were collected through structured questionnaires administered to vocational students across multiple study programs. Instrument testing demonstrated strong validity and reliability, while classical assumption tests confirmed that the regression model met the criteria for normality, linearity, and homoscedasticity. The findings reveal that financial socialization has a positive and statistically significant effect on Islamic financial literacy. The family serves as the most influential socialization agent, followed by school-based programs, peer interactions, and digital financial content. Students showed adequate understanding of fundamental Islamic financial principles—such as the prohibition of riba, gharar, and maisir—although their knowledge of more complex Sharia contracts, including mudarabah and musyarakah, remains limited. The coefficient of determination indicates that financial socialization explains a substantial proportion of the variance in Islamic financial literacy. These results underscore the strategic role of vocational education in developing ethical and Sharia-compliant financial competencies. The study recommends strengthening curriculum integration, enhancing teacher capacity, and expanding partnerships between schools and Islamic financial institutions. Systematic, value-based financial socialization is concluded to improve students’ readiness as informed consumers and prospective professionals in the Islamic finance sector, thereby contributing to Sharia-compliant financial inclusion and industry development.